2017
DOI: 10.1016/j.jadohealth.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Protective Misperception? Prospective Study of Weight Self-Perception and Blood Pressure in Adolescents With Overweight and Obesity

Abstract: Purpose Underestimating one’s weight is often seen as a barrier to weight loss. However, recent research has shown that weight under-perception may be beneficial, with lower future weight gain and fewer depressive symptoms. Here, we examine the relationship between adolescent weight under-perception and future blood pressure. Methods Using data from the National Longitudinal Study of Adolescent to Adult Health, we obtained a nationally representative sample of 2463 adolescents with overweight and obesity (st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…Our results are consistent with the findings from recent studies showing that perception of normal weight (i.e., weight underperception) was associated with lower systolic blood pressure 13 and more favorable physiological functioning (i.e., a composite measure of inflammatory, cardiovascular, and metabolic biomarkers) 10 among US youth with overweight/obesity. While these studies found no difference in the association across gender 10 , 13 , we found a stronger association between weight perception and MetS among men than women. This is contrary to our initial hypothesis that perceived normal weight (vs. perceived obesity) would be more protective among women than men given that fat bias has been found to be more strongly directed toward women than men 24 , 25 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are consistent with the findings from recent studies showing that perception of normal weight (i.e., weight underperception) was associated with lower systolic blood pressure 13 and more favorable physiological functioning (i.e., a composite measure of inflammatory, cardiovascular, and metabolic biomarkers) 10 among US youth with overweight/obesity. While these studies found no difference in the association across gender 10 , 13 , we found a stronger association between weight perception and MetS among men than women. This is contrary to our initial hypothesis that perceived normal weight (vs. perceived obesity) would be more protective among women than men given that fat bias has been found to be more strongly directed toward women than men 24 , 25 .…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, recent studies have found that being identified as overweight/obese by others (i.e., weight labeling) and by BMI report cards through BMI screening is associated with increased weight gain among US female youth 34 , 35 . By inter-relating weight stigma, identification of overweight/obese status by others or BMI report cards, and self-perception of being obese, recent studies have suggested that individuals who accurately perceive their overweight/obese status might experience negative psychological processes related with weight stigma and body dissatisfaction, which can result in weight gain and cardiometabolic dysregulations 8 10 , 13 , 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…71 Another study drawing on the same US sample showed that adolescents with overweight and obesity who self-perceived as having overweight went on to experience raised blood pressure levels relative to those who self-perceived as normal weight. 72 Likewise, in a study of Korean adults, participants who self-identified as being overweight or obese showed a worse profile for biological markers of underlying metabolic health than participants who do not identify themselves as having overweight. 47 From these studies, it is not clear whether selfidentification of overweight acts on biological health indirectly through unhealthy lifestyle behaviours or via a more direct pathway involving a chronic biological stress response.…”
Section: How Could Knowing Hurt?mentioning
confidence: 99%